If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -10 = 3y + -3 Reorder the terms: -10 + 4y = 3y + -3 Reorder the terms: -10 + 4y = -3 + 3y Solving -10 + 4y = -3 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -10 + 4y + -3y = -3 + 3y + -3y Combine like terms: 4y + -3y = 1y -10 + 1y = -3 + 3y + -3y Combine like terms: 3y + -3y = 0 -10 + 1y = -3 + 0 -10 + 1y = -3 Add '10' to each side of the equation. -10 + 10 + 1y = -3 + 10 Combine like terms: -10 + 10 = 0 0 + 1y = -3 + 10 1y = -3 + 10 Combine like terms: -3 + 10 = 7 1y = 7 Divide each side by '1'. y = 7 Simplifying y = 7
| (17+3y)-3y=17 | | Y=3y | | 5(28)-8=3y | | 3x-5/11+x+1=12(x-36)-x-6/2 | | -19/242-11x-431 | | 2(5-x)forx=2.7 | | 44x+38/11 | | 8(a+x)=b-a+6x | | 12+12X/7=X+12+5X/7 | | t+4.8=70 | | 1/2r-6=20 | | 9t-9=81 | | 16X+10X+11=26X+27-16 | | 100[0.06(x+8)]= | | p(3)=1.7 | | 40=-5w | | 2u*4x^3*5u^9x^2= | | 16X+10X+1=26X+26-1 | | 219=71-Y | | 219=7-Y | | 16X-9X+27=6+7X+35 | | 8(2+6x)=56 | | 7x-57=180-(2x+75) | | 49.86+.20x=70 | | 2(x)+2(1/2)x=30 | | 7x-57=2x+75 | | 9x-10x=-13 | | 16X-9X+27=6X+7X+35 | | (5/2z)+(6/z)=1 | | 49.83+.20x=70 | | 14c+6=48 | | 2x^5-12x^3=0 |